2013
DOI: 10.1002/bit.25139
|View full text |Cite
|
Sign up to set email alerts
|

Cel48A from Thermobifida fusca: Structure and site directed mutagenesis of key residues

Abstract: Lignocellulosic biomass is a potential source of sustainable transportation fuels, but efficient enzymatic saccharification of cellulose is a key challenge in its utilization. Cellulases from the glycoside hydrolase (GH) family 48 constitute an important component of bacterial biomass degrading systems and structures of three enzymes from this family have been previously published. We report a new crystal structure of TfCel48A, a reducing end directed exocellulase from Thermobifida fusca, which shows that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 45 publications
(76 reference statements)
1
54
0
5
Order By: Relevance
“…The processivity of the wild type TrCel7A on Avicel has been measured before (15, 22, 31), and the current result is in line with these earlier reports. We note that relationships between product profiles and processivity have been extensively discussed (4,35,37), and somewhat deviant principles for the calculation of n have been put forward (22,31,36,38). A discussion of the validity and weaknesses of these strategies is beyond the current scope, but using different approaches, we consistently found that the processivity of W38A was about 25% lower than the wild type.…”
Section: Kinetics-mentioning
confidence: 75%
See 4 more Smart Citations
“…The processivity of the wild type TrCel7A on Avicel has been measured before (15, 22, 31), and the current result is in line with these earlier reports. We note that relationships between product profiles and processivity have been extensively discussed (4,35,37), and somewhat deviant principles for the calculation of n have been put forward (22,31,36,38). A discussion of the validity and weaknesses of these strategies is beyond the current scope, but using different approaches, we consistently found that the processivity of W38A was about 25% lower than the wild type.…”
Section: Kinetics-mentioning
confidence: 75%
“…3 showed a crossover at intermediate substrate loads, it appears that a broader range of loads may be necessary to reach a conclusion on the effect of the mutation on activity. We emphasize, however, that the W38A mutants studied here for their activity against Avicel (with an intermediate crystallinity) could behave differently on other substrates and hence that further experimental work would be required to elucidate possible kinetic differences between Trp mutations near the opening (16,38,44) and (as in the middle of the catalytic tunnel, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations